Accelerating Deep Reinforcement Learning Using Human Demonstration Data Based on Dual Replay Buffer Management and Online Frame Skipping - Yeo, Sangho; Oh, Sangyoon; Lee, Minsu (2019 IEEE International Conference on Big Data and Smart Computing, BigComp 2019 - Proceedings, 2019)
Human demonstration data plays an important role in the early stage of deep reinforcement learning to accelerate the training process as well as guiding a reinforcement learning agent to learn complicated policy. However, most of current reinforcement learning approaches with human demonstration data and reward assumes that there is a sufficient amount of high-quality human demonstration data and that is not true for most real-world learning cases where enough amount of experts' demonstration data is always limited. To overcome this limitation, we propose a novel deep reinforcement learning approach with a dual replay buffer management and online frame skipping for human demonstration data sampling. The dual replay buffer consists of a human replay memory, an actor replay memory, and a replay manager. And it can manage two replay buffers with independent sampling policies. We also propose an online frame skipping to fully utilize available human data. During the training period, the frame skipping is performed dynamically to human replay buffer where the all of human data is stored. Two online frame-skipping, namely, FS-ER(Frame Skipping-Experience Replay) and DFS-ER(Dynamic Frame Skipping-Experience Replay) are used to sample data from human replay buffer. We conducted empirical experiments of four popular Atari games and the results show that our proposed two online frame skipping with dual replay memory outperforms existing baselines. Specifically, DFS-ER shows the fastest score increment during the reinforcement learning procedure in three out of four experiments. FS-ER shows the best performance in the other environment that is hard to train a model because of sparse reward.
Keywords: Buffer management; Empirical experiments; Human demonstrations; Imitation learning; Real-world learning; Reinforcement learning agent; Reinforcement learning approach; Training process; Deep Learning; Imitation Learning; Reinforcement Learning